2020
DOI: 10.1055/s-0040-1718548
|View full text |Cite
|
Sign up to set email alerts
|

The Double Stitch Everting Technique in the End-to-Side Microvascular Anastomosis: Validation of the Technique Using a Randomized N-of-1 Trial

Abstract: Background The double stitch everting (DSE) technique, in which time is won by leaving the needle inside the vessel wall in-between stitching, is a modification of the end-to-side (ETS) anastomosis in the interest of reducing anastomosis time. This ensures proper wall eversion, intima-to-intima contact, and improved suture symmetry. Materials and Methods We designed an N-of-1 randomized trial with each microsurgeon as their own control. We included 10 microsurgeons of different levels of experience w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Although several studies demonstrated that the additional time spent exercising on nonliving tissue models improves the acquisition of technical skills in microsurgery, [3][4][5] working on living tissue models remained an important aspect. 2 Additional studies were necessary to explore the relationship between training and the number of live animals used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several studies demonstrated that the additional time spent exercising on nonliving tissue models improves the acquisition of technical skills in microsurgery, [3][4][5] working on living tissue models remained an important aspect. 2 Additional studies were necessary to explore the relationship between training and the number of live animals used.…”
Section: Discussionmentioning
confidence: 99%
“…We based the training regimen on our experience of 30 years in microsurgical training and microsurgical skill acquisition. 3 According to the availability of each student, there was a minimum of one meeting/week (working weeks). The consecutive order of the training program was followed regardless of the number of weeks missed as a result of holidays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently validated the double stitch everting technique in a randomized N-of-1 trial and are happy to report that the improvement in both speed and end-result of microvascular anastomoses is considerable (Dindelegan et al, 2020). Publishing new tricks in microvascular anastomoses is important, but validating these in well-designed studies is critical.…”
mentioning
confidence: 99%